A olaria da fidelidade: a recepção de Kierkegaard na antropologia da verdade de Heschel - Ribeiro, Andre Oswaldo Valenca [UNIFESP] (2020)
This research investigates the way in which Kierkegaard was received by Heschel’s thought. A surprisingly untapped field of research. Although concentrated on a single work, his last work, A Passion for truth, this reception reverberates on Heschel’s work as a whole. Beginning by the establishment of common concerns between Kierkegaard and the polish rabbi Kotzker, Heschel constructs a whole anthropological building composed of problems and emblems based on an experimental conception of truth and faith - the so-called “life of faith". Such a building, however, is covered by an essayistic nature of writing. From our analysis of Kierkegaard-Rezeption, we developed a conceptual platform for the prospection of what we have come to refer to as Heschel's “anthropology of truth”. An anthropology that, combining faith and truth from the perspective of an experiential knowledge of God, places simultaneously an extra-worldly framework ("celestification") and an emphasis on earthly tasks, a perspective we call "existential apocalyptic". The hybridity of this perspective marks the character of Heschel's anthropology of truth as a reflexive proposal that lies in the liminality of classifications. Such liminality is already visible in the pillar of the anthropological building, in which Heschel places a both a jew and a christic in a cooperative relationship.